Efektivitas Penerapan Pasal 7 Undang-Undang Nomor 16 Tahun 2019 Tentang Syarat Batas Usia Perkawinan - Musa, Rasni A.; Hamid, Hasmiah (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research was conducted in Rum Village, Tidore Islands City, regarding the marriage age limit regulated in Article 7 of Law Number 16 of 2019, namely 19 years for men and 19 years for women. The purpose of this research is to determine and analyze the effectiveness of the implementation of Article 7 of Law Number 16 of 2019 concerning the marriage age limit in Rum Village and the factors that inhibit the effectiveness of the implementation of Article 7 of Law Number 16 of 2019 concerning the marriage age limit in Rum Village. This research is a type of empirical juridical research. This study involved seven individuals from the North Tidore Religious Affairs Office (KUA), the village head's office, the community, and individuals involved in underage marriages. Data collection techniques included observation, interviews, documentation, and triangulation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results of this study indicate that the implementation of Article 7 of Law Number 16 of 2019 concerning the minimum age for marriage in Rum Village is ineffective. The conclusion is that the law addressing the minimum age for marriage has not been implemented effectively, and factors contributing to underage marriage include premarital pregnancy, lack of education for children, environmental influences, social media, and an unfavorable economy